Developing a coherent strategy to build leadership capacity in Scottish education. (April 2018) - Hamilton, Gillian; Forde, Christine; McMahon, Margery
Leadership is central to policy ambitions for improvement in Scottish education with leadership positioned as one of the key drivers for improvement to achieve excellence and equity for all learners. To foster teacher engagement in and leadership of change and to prepare enough teachers for headship, building leadership capacity is crucial. The question we explore is: how is it possible to design a career-long leadership development strategy to secure the capacity necessary to fulfil these policy intentions while fostering the autonomy of teachers in professional learning? First, we examine leadership development in the reform agenda and second, we consider the task of balancing system and individual needs in career-long leadership development. We then detail the approaches used to build a cohesive leadership system and its ongoing development.